(untitled) (Research, Society and Development, 2021)
Objective: To describe the deaths of the elderly in the Federal District from 2008 to 2018 and analyze the main causes and related factors. Methodology: Time series study on older adults mortality, descriptive analysis and comparison of rates using the jonckheere-terpstra test. Results: The mean age was 76.51. Most deaths occurred between 80 years of age or older. Male sex predominated. The main causes of death were acute myocardial infarction (6.6%); pneumonia (5.2%); stroke (4.1%); malignant neoplasm of the bronchi or lungs (3%) and chronic obstructive pulmonary disease (2.6%). Higher mortality among men (p<0.001), from cardiovascular causes (p=0.006), and in older elderly (p<0.001) was statistically significant. Conclusion: Most deaths were due to cardiovascular causes. Being an elderly man and being older were related to higher mortality. The findings suggest that the increase in primary care coverage may have contributed to the observed pattern.